Serologic reactivity of unidentified specificity in antenatal testing and hemolytic disease of the fetus and newborn: The BEST collaborative study. Issue 4 (23rd February 2023) - Lu, Wen; Ziman, Alyssa; Yan, Matthew T. S.; Waters, Allison; Virk, Mrigender Singh; Tran, Ann; Tang, Hongying; Shih, Andrew W.; Scally, Edel; Raval, Jay S.; Pandey, Suchi; Pagano, Monica B.; et al.
Abstract: Background: The clinical significance of serologic reactivity of unidentified specificity (SRUS) in pregnancy is not clear based on available literature. The aim of this study is to determine if SRUS is associated with hemolytic disease of the fetus and newborn (HDFN). Study Design and Methods: Retrospective data were collected from eight institutions over an 11‐year study period (2010–2020), when available (5/8 sites). The outcome of the pregnancies with SRUS—no, mild, moderate, or severe HDFN—was determined. Results: SRUS was demonstrated in 589 pregnancies. After excluding those with incomplete data, a total of 284 pregnancies were included in the primary HDFN outcome analysis. SRUS was detected in 124 (44%) pregnancies in isolation, and none were affected by HDFN. Of 41 pregnancies with SRUS and ABO incompatibility, 37 (90%) were unaffected, and 4 (10%) were associated with mild HDFN. Of 98 pregnancies with SRUS and concurrent identifiable antibody reactivity(s), 80 (81%) were unaffected, and 19 (19%) were associated with mild to severe HDFN. There was 1 case of mild HDFN and 1 case of severe HDFN in the 21 pregnancies with SRUS, ABO incompatibility, and concurrent identifiable antibody reactivity(s), and 19 (90%) were unaffected by HDFN. Among all patients with repeat testing, newly identified alloantibodies or other antibodies were identified in 63 of 212 (30%) patients. Although most were not clinically significant, on occasion SRUS preceded clinically significant antibody(s) associated with HDFN (3%, 5/188). Conclusion: The antenatal serologic finding of SRUS in isolation is not associated with HDFN but may precede clinically significant antibodies.